Did banks that survived the financial crisis demonstrate better risk governance than those that did not? - Rockley, Oliver (2010)
This study explores the concept of risk governance in financial institutions and finds that banks that survived the financial crisis demonstrated better risk governance than those that did not. The global financial crisis that began in 2007 caused the worst recession since the great depression of the 1930s and engulfed much of a world, as the majority of banks suffered losses and many collapsed. Notwithstanding this, some institutions showed resilience throughout the crisis and were able to use the adverse economic conditions to their advantage. JPMorgan Chase and HSBC are examples of banks that have done particularly well from the crisis, while Lehman Brothers collapsed in September 2008 and the Royal Bank of Scotland was bailed out by the UK government a month later. This study investigates risk governance within these cases in order to determine attributes of good risk governance and to establish whether the banks that survived demonstrated better risk governance practices than the banks that did not.